The impact of burn pit waste segregation practices on respiratory and cardiovascular health risks among US military veterans deployed to Iraq and Afghanistan - Anila Bello; David A. Savitz; Christopher Rennix; Lan Jiang; Amal N. Trivedi; Gregory A. Wellenius; Susan R. Woskie (Environmental Health)
Abstract Background Open-air burning was a prevalent waste management method at many U.S. military bases during the wars in Afghanistan and Iraq. Past studies of the health impacts of burn pit exposure have relied on exposure assessments that did not account for waste segregation practices introduced in the later years of the wars, such as removing hazardous and medical waste before open burning and the use of incinerators. Objective We developed a refined exposure assessment that accounts for waste management practices on military bases and evaluated the impact of waste segregation and incineration on cardiovascular and respiratory health outcomes among veterans deployed during these conflicts. Methods The study cohort consisted of 459,381 Army and Air Force veterans who were deployed between 2005 and 2011 and received health care through the Veterans Health Administration (VHA) after deployment. The 109 most populated military bases in Afghanistan and Iraq were classified into four waste disposal categories by year: unsegregated, segregated, incineration, and no burning or incineration. Individual exposure was defined as the total number of days spent at bases based on the Department of Defense deployment histories. Health outcomes were determined through VHA healthcare records, from the end of deployment through the end of follow-up in 2020. Logistic regression was performed to investigate the association between deployment to bases with varying waste management practices and the risk of respiratory and cardiovascular diseases. Results Deployment to bases using burn pits with unsegregated waste was associated with elevated risks of hypertension and asthma, whereas deployment to bases that segregated waste or used incinerators was not. Prolonged deployment (highest duration tertile of > 240 days) to bases with unsegregated waste burning was associated with a 16% higher risk of hypertension (aOR 1.16, 95% CI 1.13-1.19) compared to those never stationed at such bases. There was a clear deployment duration-response association for hypertension, but this was not observed for asthma. Conclusions The observed increased risk of hypertension and asthma among military veterans deployed to bases that used open burning of unsegregated waste - but not among those deployed to bases that segregated waste or used incinerators - highlights the importance of considering waste management methods in future studies examining the health effects of burn pit exposures among military veterans.